A formação do professor da educação básica e a semicultura - Carvalho, Eliete Martins Cardoso de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study aims at analysing the Formation of Educational Professionals Policies of Basic Education in Brazil, in the semi-formation context. We assume that the teachers formation policies were based on the mass teachers certification in a short period of time, rather than the teachers formation itself. In this documental and bibliographic-analytical research, we initially tried to understand the historic of teachers formation in Brazil and its development from Colonial Times until now, as well as the teachers formation thematic in space and time, outlining the globalization scenery and the implications that affect education and society. This new educational context, lined from the new world order spread trough international organisms and media and state organs, unleashed a meaningful change analysis in education. Proceeding the discussion, we analyzed the Professionals Formation Policies of Basic Education in Brazil, through the Leis de Diretrizes e Bases Nacionais nº 9394/96 (Brazilian Education Basic Tenets Law) and other rules determined by MEC, which orient the professional formation of Basic Education. From this point, we described the systems created to offer these courses and the partnerships established between the Union, states, Federal District and cities, that aim at the teachers formation of Basic Education in public schools. Based on Adorno (1996) Theorie der Halbbildung (Semi-culture Theory), we also approach the semi-formation (Halbbildung) as a determination of capitalist contemporary society opposing the formation (Bildung), as well as its possible relation with the massification, the teaching cultural industry and the teacher semi-formation. The results made evident that the teachers formation policies in Brazil offer cultural formation possibilities, because the academic liberty of partners institutions remains... (Complete abstract click electronic access below)
Keywords: Professores - Formação; Educação e Estado; Industria cultural; Professores - Formação cultural; Teachers formation; Semi-formation; Educational Policies; Cultural formation; Cultural industry